2006
DOI: 10.4049/jimmunol.177.1.511
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Function of Central and Effector Memory CD4+ T Cells following Infection with a Gastrointestinal Helminth

Abstract: Immunity in the gastrointestinal tract is important for resistance to many pathogens, but the memory T cells that mediate such immunity are poorly characterized. In this study, we show that following sterile cure of a primary infection with the gastrointestinal parasite Trichuris muris, memory CD4+ T cells persist in the draining mesenteric lymph node and protect mice against reinfection. The memory CD4+ T cells that developed were a heterogeneous population, consisting of both CD62Lhigh central memory T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 54 publications
5
50
0
Order By: Relevance
“…Consistent with this, we found that Trichuris muris infection induces a population of IL-4-competent memory CD4 ϩ T cells that express CD62L (37). In contrast, we show in this study that Tcm cells generated by L. major infection can become either IFN-␥-or IL-4-producing T cells, suggesting that these cells were not derived from effector T cells.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with this, we found that Trichuris muris infection induces a population of IL-4-competent memory CD4 ϩ T cells that express CD62L (37). In contrast, we show in this study that Tcm cells generated by L. major infection can become either IFN-␥-or IL-4-producing T cells, suggesting that these cells were not derived from effector T cells.…”
Section: Discussionsupporting
confidence: 58%
“…S2b). Consistent with results from work studying CD4 T cells in 4get mice after treatment of a parasitic infection (32,33), Ϸ10-25% of the memory cells derived from GFP ϩ cells were GFP lo in some samples at the time of recovery, whereas the rest were GFP Ϫ (Fig. S2c).…”
Section: Recovered Donor Cells Generally Were Gfpsupporting
confidence: 87%
“…Although extensive studies have been performed to characterize memory CD8 T cells and Th1-polarized memory CD4 T cells (40), relatively little is currently known about the phenotype, survival, and function of memory Th2 cells. Recent publications indicated that long-term memory Th2 cells display a central memory phenotype (CD62L high CD44 high ) and provide protection against helminth and protozoan parasites (41,42). Memory Th2 cells have been shown to accumulate at the host: parasite interface during secondary infections with the helminth parasite Heligmosomoides polygyrus and might enhance parasite clearance by inducing the differentiation of alternatively activated macrophages (43,44).…”
Section: Discussionmentioning
confidence: 99%